Mandarin Language Needs Analysis for Communication in the Tire Manufacturing Industry: A Case Study at PT Sailun Manufacturing Indonesia - Putri, Sheila Maharani Tofina; Pamuji, Dian Yuni; Marsuki, Ria Riski (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This study aims to analyze the need for Mandarin language skills to support work communication in the tire manufacturing industry, with a case study at PT Sailun Manufacturing Indonesia. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation.The results of this study show that communication between local employees and Chinese supervisors is mostly conducted directly with the help of translators, as well as using alternatives such as Google Translate and hand gestures. However, these methods are not yet fully effective due to limited internet signal in the machine area and the suboptimal use of hand gestures in conveying detailed messages. The main challenge faced is the limited Mandarin proficiency of local employees, especially in speaking, listening, and reading skills. An effective strategy to overcome these challenges is Mandarin language training accompanied by individual learning motivation.These findings emphasize that mastering Mandarin is an essential need in a multinational work environment to improve communication effectiveness and work productivity.